Inovasi Jamu Jeli Anak : Metode Housewife Creative dengan Menggabungkan Semangat Kewirausahaan dan Pelestarian Tradisi Lokal untuk Meningkatkan Perekonomian Keluarga - Dyah Palupiningtyas; Krisnawati Setyaningrum N; Julian Andriani Putri; Enik Rahayu (Jurnal Pengabdian kepada Masyarakat Indonesia (JPKMI), 2023)
The role of housewives is a vital component of the nation that can be empowered to enhance family welfare. Various programs can be implemented by women to improve family well-being by utilizing and managing their surrounding environment. One such program, particularly in the realm of food, is the cultivation and utilization of local traditions, specifically the Family Medicinal Plants (TOGA) program. Prioritized issues include the availability of land for TOGA cultivation and the processing of results that still yield conventional products, limiting their economic value. The use of chemical drugs, especially for children, poses significant risks, given the prevalence of toddlers and children under 12 in residential areas. Efforts are needed to reduce the consumption of chemical drugs in favor of herbal products and to address the innovative production and management of herbal products as a priority for PKK housewives. Activities involve socialization and training using the Housewife Creative Method as a solution. The modification of conventional herbal medicine or liquid herbal medicine into gel form is considered an innovative solution, adding economic value when sold. A 3-4 month community service project in Green Semesta Housing, Wates Subdistrict, Semarang, specifically in RT 2 RW 4, targeting PKK mothers, yielded positive and beneficial results. PKK mothers, who are also homemakers, gained additional insights into the use of TOGA plants, creating economically valuable products such as jelly herbal medicine for children in various types and creative packaging. The project also provided advanced entrepreneurial knowledge related to utilizing local products like TOGA plants. All PKK mothers could predict selling prices and produce appealingly packaged jelly herbal medicine products, making them suitable for marketing and sale.